Relationship between physical activity and sarcopenia among elderly people in ten provinces (autonomous regions) of China, 2022—2023 - Yuchen WANG; Huijun WANG; Yuna HE; Chang SU; Jiguo ZHANG; Wenwen DU; Xiaofang JIA; Feifei HUANG; Li LI; Jing BAI; Yanli WEI; Xiaofan ZHANG; et al. (环境与职业医学, 2025)
BackgroundThe decline of physical activity in the elderly due to aging may increase the risk of sarcopenia. Currently, there is a lack of evidence from large natural populations on the relationship between PA and sarcopenia.ObjectiveTo explore the relationship between PA and sarcopenia in the elderly aged 60 years and above in 10 provinces (autonomous regions) of China.MethodsData were retrieved from the 2022—2023 round of the China Development and Nutrition Health Impact Cohort. Personal basic information and PA data were collected by questionnaire survey. Skeletal muscle mass was measured by bio-electrical impedance analysis, muscle strength was measured using a grip dynamometer, and physical performance was reflected by 6-meter walk speed. The Asian Working Group for Sarcopenia (AWGS) 2019 criteria were used to diagnose sarcopenia. Light physical activity (LPA) duration, moderate-to-vigorous physical activity (MVPA) duration, and total physical activity volume were calculated. A total of 3326 residents aged ≥60 years with complete data were selected as the survey participants. Multiple logistic regression models and restricted cubic splines (RCS) were used to assess the association between PA duration/volume and sarcopenia.ResultsIn 10 provinces (autonomous regions) of China, the prevalence of sarcopenia in the elderly aged 60 years and above was 5.5% (95%CI: 4.7%, 6.2%). The logistic regression analysis showed that compared with the elderly reporting 0-7.0 h·week−1 in LPA duration, the risk of sarcopenia in the elderly with LPA duration of >14.0-21.0 h·week−1 was reduced by 51% (OR=0.49, 95%CI: 0.26, 0.96). Compared with the elderly with total physical activity ≥15.0 metabolic equivalent of task (MET)-h·week−1, those with <7.5 MET-h·week−1 had a 2.24-fold increased risk of sarcopenia (OR=2.24, 95%CI: 1.17, 4.29). The RCS results found that LPA duration and total physical activity volume each showed a nonlinear dose-response relationship with the risk of sarcopenia (Poverall<0.05, Pnon-linear<0.05). Compared with the elderly with an LPA duration of 0 h· week−1, the risk of sarcopenia in the elderly with an LPA duration of 12.6 h· week−1 was the lowest (OR=0.42, 95%CI: 0.21, 0.83). Compared with the elderly with a total physical activity volume of 15.0 MET-h· week−1, the elderly with a total physical activity volume of 46.0 MET-h· week−1 had the lowest risk of sarcopenia (OR=0.57, 95%CI: 0.38, 0.84). There was no statistically significant association between weekly MVPA duration and the risk of sarcopenia (P>0.05).ConclusionIncreasing weekly LPA duration and total physical activity volume would help to reduce the risk of sarcopenia.